Signatures of Selection on Standing Genetic Variation Underlie Athletic and Navigational Performance in Racing Pigeons. (13th March 2018) - Gazda, Małgorzata A; Andrade, Pedro; Afonso, Sandra; Dilytė, Jolita; Archer, John P; Lopes, Ricardo J; Faria, Rui; Carneiro, Miguel
Abstract: Racing pigeons have been selectively bred to find their way home quickly over what are often extremely long distances. This breed is of substantial commercial value and is also an excellent avian model to gain empirical insights into the evolution of traits associated with flying performance and spatial orientation. Here, we investigate the molecular basis of the superior athletic and navigational capabilities of racing pigeons using whole-genome and RNA sequencing data. We inferred multiple signatures of positive selection distributed across the genome of racing pigeons. The strongest signature overlapped the CASK gene, a gene implicated in the formation of neuromuscular junctions. However, no diagnostic alleles were found between racing pigeons and other breeds, and only a small proportion of highly differentiated variants were exclusively detected in racing pigeons. We can thus conclude that very few individual genetic changes, if any, are either strictly necessary or sufficient for superior athletics and navigation. Gene expression analysis between racing and nonracing breeds revealed modest differences in muscle (213) and brain (29). These transcripts, however, showed only slightly elevated levels of genetic differentiation between the two groups, suggesting that most differential expression is not causative but likely a consequence of alterations in regulatory networks. Our results show that the unique suite of traits that enable fast flight, long endurance, and accurate navigation in racing pigeons, do not result from few loci acting as master switches but likely from a polygenic architecture that leveraged standing genetic variation available at the onset of the breed formation.